What Makes a Leading Case? The Narrow Lens of the Law or a Wider Perspective? - Glazebrook, Susan (Victoria University of Wellington Law Review, 2010)
This article suggests that an examination of leading cases should be extended beyond an exploration of the role that a decision has played in settling an area of law. It is also necessary to examine the social and historical implications and underpinnings of a decision. Further, a concentration on leading cases alone is too narrow a focus. The study of the ordinary run of cases can say much about the law and its relationship to society and about wider trends in society. The article illustrates these themes with a discussion of a number of leading cases in New Zealand and also of the work done by the author on criminal cases in Rouen during the French Revolution.